Tokoh-Tokoh Utsmani Muda dan Ide-Ide Modern dalam Islam - Mulyani, Sri; Dahlan, M; Rahmawati , Rahmawati (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to find out a brief history of the birth of the Ottoman Empire, young Ottoman figures and modern ideas in the Islamic world. This research method is a literature review using a qualitative approach. Data is obtained from articles published through google scholar. Data from selected articles were then analyzed using a descriptive approach to describe key findings, identify patterns and trends, and summarize key conclusions from the reviewed literature. The data analysis technique uses qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The main finding of this article is that the Ottoman Empire was founded by the Oghuz Turkish tribe, with Ertugrul as its original founder, and then continued and strengthened by his son, Uthman bin Ertugrul, who is considered the main founder of the Ottoman Empire. The ideas put forward by the Young Ottoman leaders were influential in the period of renewal after the Tanzimat period. The Young Ottomans were originally a secret group founded in 1865 with the aim of overthrowing the absolute rule of the Ottoman Empire and pushing for a constitutional government. The Young Ottoman figures were active in carrying out secret movements. Their interactions with liberal thinkers from France and England exerted a significant influence on the Young Ottoman movement. Therefore, some of the changes they propose tend to be liberal in nature